Strategic alignment, uncertainties, and realignment of project portfolios - Martinsuo, Miia; Tuominen, Siiri (Cambridge University Press, 2026)
Uncertainty in projects and their context causes various needs for changes to projects and, consequently, to the entire project portfolio. While organizations attempt to build their project portfolios in alignment with strategy, such uncertainties may require constant uncertainty monitoring and repeated strategic realignment, so that the project portfolio would serve the strategic interests of the organization over time. This chapter characterizes the pursuit of strategic alignment in project portfolio management, maps the various sources of uncertainty that may jeopardize this alignment, and reports how organizations manage uncertainties that have accumulated to a full-blown chaos, through actions of realignment. We use examples and findings from five firms’ project portfolio management, to illustrate uncertainty sources and strategic realignment. The findings show that project behavior is both a source of uncertainty and a potential mechanism for activating and promoting strategic realignment.
Cambridge Handbook of Project Behavior